2023
DOI: 10.3389/fphar.2023.1152934
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapeutic and targeted drugs-induced immunogenic cell death in cancer models and antitumor therapy: An update review

Abstract: As traditional strategies for cancer treatment, some chemotherapy agents, such as doxorubicin, oxaliplatin, cyclophosphamide, bortezomib, and paclitaxel exert their anti-tumor effects by inducing immunogenic cell death (ICD) of tumor cells. ICD induces anti-tumor immunity through release of, or exposure to, damage-related molecular patterns (DAMPs), including high mobility group box 1 (HMGB1), calreticulin, adenosine triphosphate, and heat shock proteins. This leads to activation of tumor-specific immune respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 172 publications
0
17
0
Order By: Relevance
“…In parallel, recent studies have demonstrated that specific chemotherapeutic drugs, such as doxorubicin, camptothecin, oxaliplatin and paclitaxel (Ptx) can induce immunogenic cell death (ICD) ( Lau et al, 2020 ; Vanmeerbeek et al, 2020 ; Zhai et al, 2023 ). During ICD, dying cancer cells release damage-associated molecular patterns (DAMPs) and danger signals, such as calreticulin (CRT), adenosine 5′-triphosphate (ATP) and the high-mobility group box 1 protein (HMGB1), which collectively recruit phagocytic cells and activate the immune system at the tumor site.…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, recent studies have demonstrated that specific chemotherapeutic drugs, such as doxorubicin, camptothecin, oxaliplatin and paclitaxel (Ptx) can induce immunogenic cell death (ICD) ( Lau et al, 2020 ; Vanmeerbeek et al, 2020 ; Zhai et al, 2023 ). During ICD, dying cancer cells release damage-associated molecular patterns (DAMPs) and danger signals, such as calreticulin (CRT), adenosine 5′-triphosphate (ATP) and the high-mobility group box 1 protein (HMGB1), which collectively recruit phagocytic cells and activate the immune system at the tumor site.…”
Section: Introductionmentioning
confidence: 99%
“…[ 30 ] HMGB1 is a nuclear protein that acts as an immune adjuvant by activating dendritic cells and promoting the recruitment of immune cells to the tumor microenvironment. [ 31 ] HMGB1 stimulates the production of pro‐inflammatory cytokines and chemokines, activating antigen‐presenting cells and initiating an adaptive immune response. [ 32 ] The interaction between HMGB1 and CD40 leads to the increased expression of major histocompatibility complex (MHC) class molecules and costimulatory molecules such as CD80 and CD86.…”
Section: Resultsmentioning
confidence: 99%
“…Immunogenicity can then be readily restored by adding recombinant CRT protein back to the plasma membrane surface 50 . Thus, translocation of CRT from the ER is a key determinant of anticancer immune responses, which has been exploited as a target mechanism for immunogenic chemotherapy 26,27,51 .…”
Section: Discussionmentioning
confidence: 99%